2019
DOI: 10.1111/jocn.14802
|View full text |Cite
|
Sign up to set email alerts
|

Intention to leave among staff nurses in small‐ and medium‐sized hospitals

Abstract: Aims and objectives To explore the factors associated with the intention to leave among nurses in small‐ and medium‐sized hospitals and to determine the predictors about work environment and rewards. Background Compared with large hospitals, insight into the working conditions, rewards and turnover of nurses working for these hospitals is lacking internationally. Design Cross‐sectional study design. Methods Data were obtained from the Korean Nurses Association's 2016 Welfare Policy and System Improvement Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 36 publications
3
24
1
Order By: Relevance
“…Shift work nurses in this study also presented with 1.25 times higher turnover intention, raising the need to improve working environments for shift work nurses and to introduce various flexible working arrangements so that work-life balance might be achieved. Increased overtime also significantly raised turnover intention, as shown in previous studies (Eltaybani et al 2018;Park et al 2019). In the present study, participants who had turnover intention reported an average of five hours of overtime work per week, while participants without turnover intention reported a weekly average of 4.3 hours of overtime.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Shift work nurses in this study also presented with 1.25 times higher turnover intention, raising the need to improve working environments for shift work nurses and to introduce various flexible working arrangements so that work-life balance might be achieved. Increased overtime also significantly raised turnover intention, as shown in previous studies (Eltaybani et al 2018;Park et al 2019). In the present study, participants who had turnover intention reported an average of five hours of overtime work per week, while participants without turnover intention reported a weekly average of 4.3 hours of overtime.…”
Section: Discussionsupporting
confidence: 86%
“…Turnover intention, which refers to the consideration of changing careers, is one of the critical factors leading to actual nurse turnover (Khan et al 2018). Previous studies on the turnover intention of nurses identified that turnover intention is influenced by age, work experience, salary (Park et al 2019), work environment (Nantsupawat et al 2017;Trybou et al 2015) stress and burnout (Choi et al 2019;Khan et al 2018). However, studies focusing on the psychological factors that nurses may encounter while taking care of patients are limited.…”
Section: Fundingmentioning
confidence: 99%
“…The results, then, confirm the role of mediator of work engagement [88][89][90][91]. In other studies, reward is also confirmed as having a great impact on the job satisfaction of workers [92][93][94] and protects against intention to leave [95,96].…”
Section: Discussionsupporting
confidence: 71%
“…The data used in this study were administrative hospital status data from the HIRA, which contained information regarding nurses' demographic characteristics (e.g., age, sex, license acquisition date, hired or retired date) and the structural characteristics of hospitals (e.g., hospital type, location ownership, and nurse staffing levels). Therefore, the study did not consider nurses' working conditions (e.g., salary, workload [28], and low job satisfaction [29]) or organizational characteristics (e.g., organization commitment [30] and the leadership of supervisors [31]), which were identified as factors influencing nurse turnover in many previous studies. Despite this limitation, the results derived from the representative large cohort data were very reliable.…”
Section: Discussionmentioning
confidence: 99%